Genotype Uniformity, Wild Bird-to-Poultry Transmissions, and Farm-to-Farm Carryover during the Spread of the Highly Pathogenic Avian Influenza H5N8 in the Czech Republic in 2021 - Nagy, Alexander; Černíková, Lenka; Stará, Martina; Hofmannová, Lada; Sedlák, Kamil (Viruses, 2022)
In 2020-2021, the second massive dissemination of a highly pathogenic avian influenza of the H5Nx subtype occurred in Europe. During this period, the virus caused numerous outbreaks in poultry, including in the Czech Republic. In the present study, we provide an insight into the genetic variability of the Czech/2021 (CZE/2021) H5N8 viruses to determine the relationships between strains from wild and domestic poultry and to infer transmission routes between the affected flocks of commercial poultry. For this purpose, whole genome sequencing and phylogenetic analysis of 70 H5N8 genomes representing 79.7% of the cases were performed. All CZE/2021 H5N8 viruses belonged to the 2.3.4.4b H5 lineage and circulated without reassortment, retaining the A/chicken/Iraq/1/2020 H5N8-like genotype constellation. Phylogenetic analysis suggested the frequent local transmission of H5N8 from wild birds to backyard poultry and extensive spread among commercial poultry farms. In addition, the analysis suggested one cross-border transmission event. Indirect transmission via contaminated materials was considered the most likely source of infection. Improved biosecurity and increased collaboration between field veterinarians and the laboratory are essential to limit the local spread of the virus and to reveal and interrupt critical routes of infection.
Keywords: farmy; Animals, Wild; genotyp; Farms; poultry; Genotype; avian influenza; Česká republika; nemoci drůbeže; drůbež; H5N8; ptačí chřipka u ptáků; Disease Outbreaks; Czech Republic; kur domácí; epidemický výskyt choroby; divoká zvířata; Chickens; Poultry; zvířata; HPAI; Influenza A Virus, H5N8 Subtype; Poultry Diseases; fylogeneze; Influenza in Birds; highly pathogenic avian influenza; virus chřipky A, podtyp H5N8; outbreak; Phylogeny; Animals